2022
DOI: 10.1007/s10865-022-00351-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of emotion regulation and family involvement on diabetes distress among adults with type 2 diabetes

Abstract: Adults with diabetes frequently experience diabetes related distress, which is associated with negative health outcomes. Family members are commonly involved in patients’ diabetes self-management. However, family involvement can have helpful and/or harmful effects on patients’ diabetes outcomes. Use of interpersonal strategies to regulate negative emotions may play a role in patients’ interactions with family members and experience of diabetes distress. This study examined the influences of interpersonal emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…At this time, it is particularly important for family members to guide patients to learn self-integration, such as developing personal hobbies, learning to vent and make reasonable plans together. F4 “Affection” had the strongest positive correlation with M1 “Self –integration.” This is consistent with the study that the higher the degree of family participation is, the more care for the patient, and the better the patients' regulation strategy ( 53 ). Affection refers to the emotional degree of mutual care and love among family members ( 35 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At this time, it is particularly important for family members to guide patients to learn self-integration, such as developing personal hobbies, learning to vent and make reasonable plans together. F4 “Affection” had the strongest positive correlation with M1 “Self –integration.” This is consistent with the study that the higher the degree of family participation is, the more care for the patient, and the better the patients' regulation strategy ( 53 ). Affection refers to the emotional degree of mutual care and love among family members ( 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…F4 "Affection" had the strongest positive correlation with M1 "Self -integration." This is consistent with the study that the higher the degree of family participation is, the more care for the patient, and the better the patients' regulation strategy (53). Affection refers to the emotional degree of mutual care and love among family members (35).…”
Section: Discussionsupporting
confidence: 88%
“…Beneficial family involvement can improve the physical and mental health of diabetic patients, enhance their self-management ability and improve their glycaemic control. 43 Therefore, health care professionals should pay attention to patients’ family support, improve family health education, help solve problems regarding family management, and promote good family function.…”
Section: Discussionmentioning
confidence: 99%
“…Di Giacomo and colleagues [ 1 ] examined the impact of psychological aspects within the scope of hypertension management via the lens of the relationship between emotion regulation and self-care skills. Similarly, Leukel et al [ 2 ] investigated the role of emotion regulation in relation to diabetes-related distress management. Both studies found the significant influence of emotion regulation on enhancing self-care skills and promoting improved psychological outcomes.…”
Section: Introductionmentioning
confidence: 99%